Utilization of IoT for Waste Transportation Optimization Through a Web-Based Monitoring System - Kilimandang, Jendry; Rambu Yetti Kalaway; Leonard Marten Doni Ratu, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Ineffective waste management can lead to waste of resources, accumulation of waste, and inefficient mobility of cleaning staff. The current waste transportation system is still carried out routinely without considering the fullness of the bins, causing a waste of fuel and labor. This research aims to develop an Internet of Things (IoT)-based trash bin monitoring system and Web application to improve the efficiency of waste management. The system uses ultrasonic sensors to detect the fullness level of bins and sends real-time data to a Web-based monitoring platform. The system is also equipped with an automatic notification function to notify the janitor when the bin is full. This research uses the Research and Development (R&D) method for IoT system development and the Extreme Programming (XP) method for Web application development. The eXPected result is a system that can reduce the number of unnecessary trips, reduce operational costs, and improve overall environmental cleanliness. With this system, waste management is eXPected to be more efficient, sustainable, and environmentally friendly.